Prove that 2 cot (2x) + tan(x) == cot (x)

(1) Aim to rearrange the right hand side (rhs) to make it look like the left hand side.LHS = 2 cot (2x) + tan (x)(2) Notice that the rhs is only in terms of x, whereas the right has a function involving 2x. Therefore use trig identities to make the RHS in terms of x onlycot (2x) = 1 / tan (2x) = [1 - tan 2 (x)]/[(2 tan (x))]ThereforeLHS = [1 - tan 2 (x)]/[ tan (x)] + tan (x) = 1 / tan(x) = cot (x) = RHS, as given.

Answered by Joseph C. Maths tutor

9643 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

How do I find the co-ordinates and nature of the stationary points on a curve?


∫(3x+4)2dx


What is differentiation?


When do you know to use integration by parts?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences